Effect of corroded stirrups on shear behavior of reinforced recycled aggregate concrete beams strengthened with carbon fiber-reinforced polymer. (15th March 2019) - Zhang, Huifeng; Wu, Jin; Jin, Fengyu; Zhang, Chengjun
Abstract: This paper reports the effect of corroded stirrups on the shear behavior of reinforced recycled aggregate concrete (RRC) beams strengthened with carbon fiber-reinforced polymer (CFRP). Eight beams were subjected to accelerated corrosion for 1, 2, 3, 4, 5, 6, and 7 days to obtain the theoretical mass loss in their stirrups of 1%, 3%, 5%, 7%, 9%, 11%, and 13%, respectively. The results indicated that the shear capacity of the RRC beams strengthened with CFRP improved more significantly. The corroded RRC beams, strengthened by adhering CFRP sheets, could restrict the development and extension of the diagonal cracks and delayed the occurrence of the critical cracks. The specimens failed owing to the debonding of CFRP, and subsequently, the concrete was crushed. The CFRP did not reach its ultimate strength. The CFRP strengthening effect of corroded RRC beams was more obvious than that of corroded reinforced concrete (RC) beams under the same corrosion level. The maximum deflection of the strengthened corroded beam was increased by 30% compared with the strengthened uncorroded beam. With increased stirrup corrosion level, the specimen's deflection was increased. In addition, equations were proposed for calculating the shear capacity of the beam, which was in good agreement with the experimental results.